From war to peace: socio-historical context and current challenges for the public administration in the Federal Republic of Yugoslavia (Serbia and Montenegro) - Koch, Ulrich; Jovanovic, Goran (1997)
This article focuses on the role of the public administration in a period of profound structural and rapid day-to-day political and economic changes in the Federal Republic of Yugoslavia (Serbia and Montenegro). In order to attain a `contextual' view the sociohistorical context of public administration is discussed. The concept of transformation, as it is usually used to describe the changes in post-socialist countries, is broadened by applying the concept of integration. Some of the manifold deficiencies in public administration in the Federal Republic of Yugoslavia are analysed. At the present stage, the administration does not seem to be able to deliver integration or play an active role in either economic development or social peace. As instruments in the reform of the public administration, institutional pluralism, according to subsidiarity, and intercultural human resource management are proposed. - Reproduced
Keywords: Public administration - Yugoslavia; Public administration